The Corporate Elasticity of Taxable Income: Event Study Evidence from Switzerland - Matthias Krapf; David Staubli (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We estimate the corporate elasticity of taxable income. Our analysis draws on panel variation in the decentralized system of corporate taxation in Switzerland. We find that an increase in a jurisdiction's corporate net-of-tax rate by 1% results in an increase in aggregate corporate income by about 3.5% over a time span of 4 years. The elasticity is larger in remote, non-central locations. Firm entry, exit, and mobility only account for a small share of the overall elasticity.
Keywords: H21; H25; H32; 330; corporate income tax; tax elasticity; fiscal federalism